2023
DOI: 10.1002/bies.202300040
|View full text |Cite
|
Sign up to set email alerts
|

New paradigms in actomyosin energy transduction: Critical evaluation of non‐traditional models for orthophosphate release

Abstract: Release of the ATP hydrolysis product ortophosphate (Pi) from the active site of myosin is central in chemo‐mechanical energy transduction and closely associated with the main force‐generating structural change, the power‐stroke. Despite intense investigations, the relative timing between Pi‐release and the power‐stroke remains poorly understood. This hampers in depth understanding of force production by myosin in health and disease and our understanding of myosin‐active drugs. Since the 1990s and up to today,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 105 publications
1
2
0
Order By: Relevance
“…Our conclusion that force develops before Pi release and that the same force is maintained after Pi release on myofibrils is consistent with previous observations on fast-twitch single fibers [31,7,61,60,36], slow-twitch single fibers [33,64], and single molecule experiments [70]. This conclusion is at variance with that of X-ray crystallographic studies [38] (see also [45,41]), which concluded that force develops after Pi release. There may be several reasons for this disparity.…”
Section: Force Associated With Each Cb Statesupporting
confidence: 91%
“…Our conclusion that force develops before Pi release and that the same force is maintained after Pi release on myofibrils is consistent with previous observations on fast-twitch single fibers [31,7,61,60,36], slow-twitch single fibers [33,64], and single molecule experiments [70]. This conclusion is at variance with that of X-ray crystallographic studies [38] (see also [45,41]), which concluded that force develops after Pi release. There may be several reasons for this disparity.…”
Section: Force Associated With Each Cb Statesupporting
confidence: 91%
“…Moreover, blocking orthophosphate from reaching the exit tunnel with the mutation S217A or exposure to high concentrations of orthophosphate affected neither the size nor the rate of the power stroke, implying that the power stroke occurs before orthophosphate enters the exit tunnel [ 64 ]. However kinetic models showed that the timing of orthophosphate release from the active state after the power stroke was not consistent with experimental observations of the [Pi]-independence of maximal shortening velocity and monotonous decrease in isometric force with increased [Pi] [ 62 , 65 ]. This led to the multi-step orthophosphate release kinetic model, which predicts that orthophosphate leaves the active site but is trapped at an intermediate secondary binding site before completion of the power-stroke [ 65 ].…”
Section: Discussionmentioning
confidence: 77%
“…In our adaptation of the Davydov soliton model, straightening of the relay helix is proposed to be an early step in the power stroke that is initiated within picoseconds of ATP hydrolysis by energy transfer from the vibrationally excited orthophosphate molecule to the relay helix. Whether orthophosphate release from the active site occurs before or after the power stroke is a highly debated issue [ 61 , 62 ]. It has been determined experimentally by Förster resonance energy transfer (FRET) studies that the timescale for orthophosphate release ranges from 3 to 50 ms and that the timescale for the power stroke is 2–3 ms [ 61 ].…”
Section: Discussionmentioning
confidence: 99%